2019
DOI: 10.3390/w11081549
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Effects of Salinization on Compound Release from Drained and Restored Coastal Wetlands

Abstract: Over the past two decades, great efforts have been made to restore coastal wetlands through the removal of dikes, but challenges remain because the effects of flooding with saline water on water quality are unknown. We collected soil samples from two adjacent coastal fen peatlands, one drained and diked, the other open to the sea and rewetted, aiming at assessing the mobility and export of various compounds. Microcosm experiments with constant flow-through conditions were conducted to determine the effluent co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The temperature and pH of the soil have significant effects on the kinetics release of dissolved organic carbon 60 . Many studies found that electrical conductivity plays a vital role in mobilizing and releasing DOC in different soils 61 , 62 . The increased value of half-life required for DOC loss by leaching is probably due to DOC sorption on the surfaces of organic and inorganic colloids in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature and pH of the soil have significant effects on the kinetics release of dissolved organic carbon 60 . Many studies found that electrical conductivity plays a vital role in mobilizing and releasing DOC in different soils 61 , 62 . The increased value of half-life required for DOC loss by leaching is probably due to DOC sorption on the surfaces of organic and inorganic colloids in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Their basic character would have been conducive to the presence of organic matter within them [31,32]. The same would be true of the very shallow depth of this lake system favouring exchanges between the water column and surface sediments [33] and the low salinity of these waters [34,35]. However, the relatively high temperature and the reductive character of these waters would contribute to the partial degradation and mineralization of organic matter within them [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In GDS, industrial, domestic and, hospital discharges, very loaded with organic matter, would lead to a very high organic load in these waters. This would be even more so with the proliferation of aquatic plants and the strong exchanges between sediments and the water column in this season [33]. The basic character of these waters in this season would also have contributed to a relative importance of organic matter within them by partial inhibition their degradation [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…All 32 undisturbed soil cores (diameter of 8 cm, length of 5 cm) from both sites were collected by cutting the soil with a sharp knife in front of cylinder, which was slowly inserted into the soil in either horizontal or vertical direction. Cylinders were then removed from the soil by excavating a large soil block, from which the cylinders were carefully removed (Liu & Lennartz, ). The soil cores were sealed on both ends with lids and tape before being neatly placed in a cool box and transported back to the laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…In more pristine peat, the dominant flow and transport direction depends on the peat forming process and how dying plants and decaying plant materials were deposited. With advancing peat degradation, the volume fraction of macropores and pore connectivity decrease significantly (Liu & Lennartz, , ; Liu et al, ) resulting in a relative isotropic structure of highly degraded peat soils (Kechavarzi, Dawson, & Leeds‐Harrison, ; Liu et al, ). In addition, cracks occur in peat soils in dry summers, which may increase macroporosity of peat soils (Holden, Burt, & Cox, ).…”
Section: Introductionmentioning
confidence: 99%